Membentuk Kepribadian Islam melalui Strategi Komunikasi Lembaga Dakwah Kampus (LDK) di STMIK Budi Darma Medan - Imam Saputra; Fitri Aisyah Ritonga; Ahmad Tamrin Sikumbang; Zainun Zainun (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2020)
Personality as an integration of one’s tendency to behave, act and behave. The personality referred to in this case is the personality of honesty and istiqomah which is in accordance with the teachings of Islam and is called the personality of Islam. This study aims to describe the communication strategies of Campus Da'wah Institutions in shaping the Islamic personality of students, as well as the supporting and inhibiting factors of the campus Da'wah Communication strategy in shaping the Islamic personality of STMIK Budi Darma Medan students. The research method used in this study is a qualitative method by analyzing and making interpretation of data found through interviews. The data that has been collected is checked for validity, the data analysis technique starts from reducing the data and making conclusions from the results of the study. The results of this study are that to develop a communication strategy must begin with planning, implementation and of course in this strategy there are supporting and inhibiting factors. The communication strategy of Campus Propagation Institute in shaping the Islamic personality of students by planning and implementing activities that are Islamic by instilling the values of Islamic personality to students. Islamic personality here is the personality of honesty, responsibility, initiative and istiqomah in the daily life of students. Strategies that LDK does include mentoring, recitation and sharing among others. Supporting and inhibiting factors in the Campus Da'wah Institute strategy are good responses from students, while the inhibiting factor is the lack of funds. Kepribadian sebagai integrasi dari kecenderungan seseorang dalam bersikap, bertindak dan berperilaku. Kepribadian islam merupakan kepribadian tentang kejujuran, tanggungjawab, inisiatif dan istiqomah yang sesuai dengan ajaranajaran Islam. Penelitian ini bertujuan untuk mengetahui strategi komunikasi Lembaga Dakwah Kampus dalam membentuk kepribadian Islam mahasiswa, serta faktor pendukung dan penghambat dari strategi komunikasi Lembaga Dakwah Kampus. Metode penelitian yang digunakan dalam penelitian ini adalah metode kualitatif dengan menganalisis dan membuat interpretasi data yang ditemukan melalui hasil wawancara. Data yang telah dikumpulkan diperiksa keabsahannya, teknik analisa data dimulai dari mereduksi data dan membuat simpulan hasil penelitian. Hasil dari penelitian ini mendeskripsikan strategi komunikasi Lembaga Dakwah Kampus dalam membentuk kepribadian Islam mahasiswa. Bentuk-bentuk strategi komunikasi adalah komunikasi antar personal dan komunikasi tidak langsung yaitu dakwah berbasis materi dan dakwah berbasis media. Faktor pendukung dalam strategi Lembaga Dakwah Kampus ini yaitu respon yang baik dari mahasiswa, pengurus LDK memiliki potensi yang lebih, LDK Al-Hayyan memiliki susunan struktur anggota keorganisasian yang jelas sedangkan faktor penghambatnya yaitu masalah kurangnya dana dalam program LDK, kurangnya waktu untuk bersosialisasi dan semangat anggota LDK yang menurun.